Mucinous cystadenoma and cystadenocarcinoma of the vermiform appendix with particular reference to mucocele and pseudomyxoma peritonei - Gibbs, N. M. (1973)
Ten cases of mucocele of the vermiform appendix are described. Eight cases were of mucinous cystadenoma of the appendix and six cases showed acute inflammation. Two of the six cases showed pseudoinvasion of the appendix and in a further case the appendix had perforated with extrusion of a misplaced neoplasm. Two cases were of mucinous cystadenocarcinoma and one of these was diagnosed as `pseudomyxoma peritonei'. `Pseudomyxoma peritonei' is a misnomer and is caused by dissemination of a mucinous cystadenocarcinoma within the peritoneal cavity. The special problems of histological diagnosis are discussed.